Respons fisiologis benur udang vaname (Litopenaeus vannamei) terhadap penambahan kalsium selama adaptasi di salinitas rendah - Taqwa, Ferdinand Hukama; Fitrani, Mirna; Purwanto, Rudi (Universitas Malikussaleh, 2021)
The purpose of this study was to determine the optimum addition of calcium during the adaptation period of white shrimp seed in low salinity media, so the physiological conditions of shrimp still support maximally survival and growth. The research was carried out by using the Completely Randomized Design, i.e., the addition of calcium in freshwater for decreasing water salinity from 20 g L-1 to 0.5 g L-1 as much as 150, 200, 250, 300, and 350 mg L-1, respectively. The freshwater used in the salinity reduction process was based on previous research that included sodium and potassium additions of 75 mg L-1 and 50 mg L-1, respectively. The test animal was a white shrimp stadium PL15 that had been acclimated for 5 days to a medium salinity of 20 g L-1. The results of this study showed that the addition of 300 mg L-1- calcium in freshwater during the adaptation for 96 hours significantly accelerate the achievement of molting time (1360 minutes), suppress the stress levels and metabolism rate (body fluid glucose of 169.80 mg L-1 and oxygen consumption level of 0.95 mg O2 g-1 h-1), and produce the highest survival rate of white shrimp seed (99%).Keywords: adaptation, calcium, low salinity, physiology, white shrimp